Interventions to lower cardiovascular disease risk factors among Asian Indian immigrants: a scoping review protocol - Abeer M Mobarki; Karen T D’Alonzo; Maya E Joseph; Anju Wadhawan; Shailja Mathur; Cheryl Holly (BMJ Open)
Introduction To identify effective interventions to lower cardiovascular disease (CVD) risk factors among Asian Indian (AI) immigrants.As the second largest immigrant group in the USA, AI immigrants experience CVD prevalence rates as high as 13% among males and 4.4% among females; these rates are significantly higher than other Asian subgroups and the general US population. Despite extensive knowledge of CVD risk factors, there have been few cardioprotective interventions in this population.Methods and analysis Interventional studies of first-generation AI immigrants aged 18–70 years, conducted between 2000 and 2025, will be identified, including randomised controlled trials, factorial and cross-over designs, and cluster randomised trials. We will include AIs with and without a specific family history of CVD, or personal history of type 2 diabetes mellitus, hyperlipidaemia or obesity. Exclusion criteria include AIs born in the USA or visiting.The Arksey and O’Malley methodology framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews will be used for analysis. A preliminary review of interventions to lower the CVD risk in AIs will guide the research questions (stage 1). Relevant articles published between 2000 and 2025 will be retrieved using electronic databases and search terms (stage 2). Two independent reviewers will select studies based on eligibility criteria (stage 3). Reviewers will determine eligibility status, screen full texts and retrieve relevant publications. Reviewers will extract data, capturing study design, sample characteristics, types of interventions, outcomes and key findings (stage 4). A summary of results will be presented (stage 5). The review will identify the most effective interventions, potential areas for future research and practical recommendations to improve CVD outcomes among AI immigrants.Ethics and dissemination Included studies will meet ethical standards in research. Findings will be disseminated through manuscripts, presentations at relevant conferences and community outreach programmes to promote effective interventions.